Development of low density polyethylene/sago based biofilm via blow film molding technique - Wan Abdul Rahman, Wan Aizan; Rasit Ali, Roshafima; Jamaluddin, Jamarosliza; Mohamad, Ida Idayu (Faculty of Chemical and Natural Resource Engineering, 2009)
The aim of this study is to develop degradable starch based packaging film with enhanced mechanical properties. A series of low density polyethylene (LDPE)/sago starch compounds with various sago starch contents were prepared by twin screw extrusion with the addition of maleic anhydride grafted polyethylene as compatibilizer. Palm cooking oil was used as processing aid to ease the blown film process, thus, degradable film can be processed via conventional blown film machine. Studies on their characteristics, mechanical properties and biodegradation were carried out by Fourier Transform Infrared (FTIR) spectroscopy and optical properties, tensile test and exposure to fungi environment and soil burial analysis respectively. The presence of high starch contents had an adverse effect on the tensile properties of LDPE/tapioca starch blends. However, the addition of compatibilizer to the blends improved the interfacial adhesion between the two materials, hence, improved the tensile properties of the films. High content of starch also was found to increase the rate of biodegradability of LDPE/tapioca starch films. It can be proved by exposure of the film to fungi environment and weight losed in soil burial analysis. A growth of microbes colony can be seen on the surface of LDPE/tapioca starch film indicates that the granular starch present on the surface of the polymer film is attacked by microorganisms, until most of it is assimilated as a carbon source.